2017
DOI: 10.1111/coa.12981
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of synchronous bilateral tonsil squamous cell carcinoma: A retrospective study

Abstract: Objectives The prevalence of synchronous bilateral tonsil cancer remains unexplored. To date, only 38 cases have been described in the literature. With an aim to substantiate the Danish recommendation of performing bilateral tonsillectomy in patients with suspected or proven tonsil cancer and in patients with cervical carcinoma metastasis from an unknown primary tumour, this study was undertaken to determine the prevalence of synchronous bilateral tonsil cancer. Design A retrospective review of all patients di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(52 citation statements)
references
References 21 publications
1
50
1
Order By: Relevance
“…In the Rokkjaer and Klug study, when contralateral tonsillectomy was routinely performed for all patients with known or suspected tonsillar cancer, 2.3% had contralateral disease. 5 Finally, it is not evident that subclinical contralateral tonsil cancer would ultimately have clinical impact. A majority of patients receive adjuvant radiation and close post-treatment surveillance.…”
mentioning
confidence: 99%
“…In the Rokkjaer and Klug study, when contralateral tonsillectomy was routinely performed for all patients with known or suspected tonsillar cancer, 2.3% had contralateral disease. 5 Finally, it is not evident that subclinical contralateral tonsil cancer would ultimately have clinical impact. A majority of patients receive adjuvant radiation and close post-treatment surveillance.…”
mentioning
confidence: 99%
“…To determine the prevalence of SBTC, Rokkjaer et al performed a retrospective review of all patients diagnosed with TSCC between 2000 and 2015 at Aarhus University Hospital, Denmark. They found that seven of 211 (3.3%) consecutive patients with tonsil cancer who had either undergone bilateral tonsillectomy (n = 180) or unilateral tonsillectomy (clinically normal side) combined with contralateral tonsil biopsy (clinically suspicious side) (n = 31) had SBTC.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These recommendations are based on three case reports (level 4 evidence) and two retrospective chart reviews (level 3 evidence).…”
Section: Level Of Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…Very few patients with tonsillar carcinoma present with bilateral HPV+ tumors, and the literature on this phenomenon is somewhat limited [ 16 – 20 ]. A recent retrospective study reported that in a cohort of Danish patients, only 3.3% had synchronous bilateral tonsil cancer [ 21 ]. There are multiple hypotheses on the mechanism of this event.…”
Section: Introductionmentioning
confidence: 99%